DISKURSUS NASIONALISME DAN DEMOKRASI PERSPEKTIF ISLAM - Zetty Azizatun Ni’mah (IAIN Kediri, 2016)
Nationalism and democracy as a political thought brought by the West raises various intellectual responses in the world of Islam, created the idea of pros and cons that have no end to be discussed. The pro assume that the idea of nationalism and democracy even if brought by the West turns its values can be adjusted to Islam, otherwise the opponent assumes ism brought by the West is aiming to dominate the Islamic world, various of arguments they put forward to respond to the two political thought. There is some debate over the relationship between Islam and democracy, appeared three different camps among Muslims. The first stronghold represented by those who explicitly reject the concept of democracy in any form. The second camp is represented by those who accept democracy based approach Normative that Islam contains elements of a democratic ideal. The most popular argument is the doctrine of shura baseline drawn from several passages in the Qur’an. The third are those who stand midway between receive and reject some aspects of democracy.Keywords; Nationalism, Democracy, Islamic Perspective